Sistem Pendukung Keputusan Rekomendasi Tempat Wisata Menggunakan Metode TOPSIS - Setiawansyah, Setiawansyah (PT. SNN MEDIA TECH PRESS, 2022)
This study aims to recommend tourist attractions using criteria of distance, travel time, entrance fees, and cleanliness by applying the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method in providing recommendations for a decision. TOPSIS is a multi-criteria decision-making method used to select the best alternative from a group of alternatives based on predetermined criteria. The results of the ranking of recommended tourist attractions that get rank 1 are Parks and Historical Places with a value of 0.673, rank 2 is Swimming Pool with a value of 0.597, rank 3 is Beach with a value of 0.504, and rank 4 is Mountain with a value of 0.409.